Diagnostics of anxiety and dermatological index of life quality in patients with chronic actinic dermatitis - P. E. Konnov; E. V. Orlov; L. I. Mostovaya; A. A. Arsenyeva (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
65 patients with chronic actinic dermatitis were examined, with the determination of dermatological and psychological indices, allowing to determine the quality of life and the severity of depressive and anxiety disorders in patients.